Analisis Pengaruh Tingkat Perkembangan Moral terhadap Tax Complience - Arianti Fakhriana; Eka Fauzihardani (Universitas Negeri Padang, 2024)
This study aims to examine the effect of moral development on tax compliance. The test uses primary data with a sample of 390 students in the city of Padang. Statistical tests performed were multiple regression tests and anova tests. Testing using multiple regression shows that hypotheses 1 and 2 are accepted. Meanwhile, hypothesis 3 is rejected. Anova testing shows that hypotheses 4 and 5 are accepted. This test shows that the level of tax compliance in Indonesia is dominated by preconventional moral developments such as sanctions and punishments.